Comprehensive analysis and exploratory design of graphene-based subharmonic mixers operating at the gigahertz band - M. C. Pardo; F. Pasadas; A. Medina-Rull; M. G. Palomo; S. Ortiz-Ruiz; E. G. Marin; A. Godoy; F. G. Ruiz (Discover Nano)
Abstract Ambipolar conductance in graphene field-effect transistors (GFETs), and in particular their quasi-quadratic I–V transfer characteristic, makes these devices excellent candidates for exploiting subharmonic mixing at high frequencies. Several realizations have already demonstrated the ability of GFETs to compete with, or even improve, state-of-the-art mixers based on traditional technologies. Nonetheless, a systematic analysis of the influence on performance of both circuit design and technological aspects has not been conducted yet. In this work, we present a comprehensive assessment of the conversion losses by means of applying radio-frequency circuit design techniques in terms of filtering and matching, along with the impact stemming from physical and geometric variations of a fabricated graphene technology.